Newness, Imperialism, and International Legal Reform in Our Time: A TWAIL Perspective - Obiora Chinedu Okafor (My University, 2016)
This article examines, from a critical Third World Approaches to International Law (TWAIL) perspective, the highly consequential claim that the terrorist attacks on the United States on September 11, 2001 (“9/11”) inaugurated a new era of international relations in so radically significant a way as to justify the retrenchment or severe weakening of certain fundamental, indeed constitutional, norms of international law, such as: the absolute ban on the practice of torture, the prohibition of the unilateral use of force by states, and the ban on pre-emptive strikes. The article thus focuses on the “newness claim” that is often made in justification of the touted necessity of such reforms, and on the important insights that TWAIL analysis provides regarding the coherence, legitimacy, and sustainability of this newness claim. The article argues three things. First, that the newness claim is best understood as a deeply political practice. Next, that only by discounting the broadly shared historical experiences of many “third-world” peoples can the 9/11 attacks be seen as inaugural of a world order that is so significantly new or different as to necessitate the retrenchment or sever weakening of fundamental international law norms. Finally, the article argues that TWAIL remains an extremely useful, if not invaluable, international law optic that allows us to understand much better, and respond much more adequately to, the sophisticated and subtle processes through which these kinds of newness claims are deployed in order to render otherwise untenable reforms of the international legal order seemingly necessary and even imperative.